Migration of Bima People to Makassar 1975 - 2007 - Bustan; La Malihu; Rasyid Ridha; Jumadi; Bahri (Technium Social Sciences Journal, 2023)
This paper aims to describe the migration of the Bima people to the city of Makassar (1975 - 2007), by explaining the background of the migration and the reasons why Makassar was chosen as the destination. Likewise, it explores the migration process of the Bima people, as well as the pattern of adaptation of the Bima people in overseas areas in Makassar. This study uses historical methods which include heuristics or data collection obtained through interviews, observation and documentation. Furthermore, criticism was made of the sources that had been collected, then interpreted or given an interpretation of these sources as well as historiography or historical writing which in turn gave birth to writings about the migration of the Bima people to Makassar (1975-2007). The results showed that the migration background of the Bima people to Makassar was influenced by the geographical conditions of Makassar city and also the historical relationship between Bima and Makassar. As for the reasons Makassar was chosen as a migration destination in order to continue education. The migration process of the Bima people to Makassar is not group but individual and has 3 motives, namely permanent, semi-permanent, and circular migration. As for the adaptation pattern of the Bima people so that they feel at home living in Makassar, namely adapting themselves and adapting to the local culture.